Ni–Ti Nanocomposite Coatings Electro-Codeposited from Deep Eutectic Solvent Containing Ti Nanoparticles. Issue 4 (12th February 2020) - Hou, Yuanyuan; Peng, Zhenjun; Liang, Jun; Fu, Shaohai
Abstract : In this work, Ni–Ti composite coatings with well-decentralized Ti were firstly prepared by electro-codeposition with pulse current in deep eutectic solvent (DES) synthesized by choline chloride (ChCl) and ethylene glycol (EG) containing Ti nanoparticles. The electrochemical mechanism of Ni 2+ deposition in the presence of Ti nanoparticles in DES were investigated. Moreover, the influences of Ti nanoparticle loading, current density and duty cycle on the levels of Ti nanoparticles loaded into the Ni matrix were systematically explored, in which the contents of Ti nanoparticles could achieve as high as 10.77 wt% when the loading of Ti nanoparticles was only 16 g·l −1 with current density of 5 mA·cm −2 (Frequency = 1000 Hz, Duty cycle = 1/4). Besides, the structure morphology, crystal size and thickness of the composite plating varied with the content of the loaded Ti nanoparticles were studied. Furthermore, the anticorrosion performance of the Ni–Ti plating was significantly improved as the content of doping Ti nanoparticles increased.